Financial reporting in times of crisis: The case of the Serbian developing economy during COVID-19 - Vladimir Obradovic; Milan Cupic; Dragomir Dimitrijevic (Australian journal of management, 2024)
This study examines the impact of the COVID-19 pandemic on financial reporting in Serbia from the perspective of preparers of financial statements. Notably, the pandemic affected financial reporting in Serbia and preparers faced more professional difficulties during than before the pandemic. Financial reporting problems regarding future expectations and uncertainty are an important source of concern for preparers. The preparers who apply International Financial Reporting Standard (IFRS) for Small and Medium-sized Entities (SMEs) perceive some more difficulties than those who apply full IFRSs. This study contributes to the scarce literature regarding the impact of the COVID-19 pandemic on financial reporting.